Tinjauan Opini Pasien Rawat Jalan Terhadap Aplikasi E-Dokter di RSUD Dr. RM Djoelham Binjai Tahun 2022 - Angelia Putriana; Laila Syahfitri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Opinion is an absorption from a foreign language (opinion) It is an open response or answer to a problem stated in words (intangible), both in the form of written and oral opinions. The E-Doctor application is an online registration system for outpatients, by applying the practice appointment method. The purpose of this study was to determine the opinion of outpatients on the e-doctor application at RSUD Dr.R.M Djoelham Binjai. This type of research is quantitative research with a descriptive approach. This research was conducted from May to August 2022. This research was carried out at RSUD.Dr.RM. Djoelham Binjai. The population in this study were all patients in outpatient services in May-August 2022. The sampling technique used by researchers in this study was purposive sampling technique. The technique used in collecting this data is by using the questionnaire method. Of the 97 people, there are 37 patients who know the E-Dokter application, and among those 37 people only 10 people use and understand how to use the E-Dokter application. There are 60 people who are completely unaware of the E-Doctor application at RSUD Dr R.M Djoelham Binjai. Therefore, it is necessary to socialize the E-Doctor application to outpatien.